Using Health Check Data to Understand Risks for Dementia and Cognitive Impairment Among Torres Strait Islander and Aboriginal Peoples in Northern Queensland—A Data Linkage Study - Thompson, Fintan; Russell, Sarah G.; Harriss, Linton R.; Esterman, Adrian; Taylor, Sean; Quigley, Rachel; Strivens, Edward; McDermott, Robyn (Frontiers in Public Health, 2022)
Objective High rates of dementia are evident in First Nations populations, and modifiable risk factors may be contributing to this increased risk. This study aimed to use a longitudinal dataset to gain insights into the long-term risk and protective factors for dementia and cognitive impairment not dementia (CIND) in a Torres Strait Islander and Aboriginal population in Far North Queensland, Australia. Study Design and Setting Probabilistic data linkage was used to combine baseline health check data obtained in 1998/2000 and 2006/2007 for 64 residents in remote communities with their results on a single dementia assessment 10–20 years later (2015–2018). The relationship between earlier measures and later CIND/dementia status was examined using generalized linear modeling with risk ratios (RRs). Due to the small sample size, bootstrapping was used to inform variable selection during multivariable modeling. Results One third of participants (n = 21, 32.8%) were diagnosed with dementia (n = 6) or CIND (n = 15) at follow-up. Secondary school or further education (RR = 0.38, 95% CI 0.19–0.76, p = 0.006) and adequate levels of self-reported physical activity (RR = 0.26, 95% CI 0.13–0.52, p < 0.001) were repeatedly selected in bootstrapping and showed some evidence of protection against later CIND/dementia in final multivariate models, although these had moderate collinearity. Vascular risk measures showed inconclusive or unexpected associations with later CIND/dementia risk. Conclusions The preliminary findings from this small study highlighted two potential protective factors for dementia that may be present in this population. A tentative risk profile for later CIND/dementia risk is suggested, although the small sample size limits the applicability of these findings.